INTERVENSI GURU TERHADAP PESERTA DIDIK YANG MENGALAMI KECENDERUNGAN DYSLEXIA - Melvita Ayu Febriasari; Satrio Budi Wibowo; Achmad Irfan Muzni (Universitas Muhammadiyah Metro, 2024)
The purposeof this studywas to determine teacher intervention for students with dyslexia tendencies at SD Negeri 2 Bumi Ayur. This type of research is a descriptive case study using a qualitative approach. The data subjects are class teachers and parents of students. The data obtained by the researcher through the interview method to the research subject. Data analysis uses data collection, data reduction, data presentation, and drawingconclusions. Validity testing can be doneby means of triangulation of sources. The conclusions in thisstudy are (1) Teacher's Direct Intervention at SD Negeri 2 Bumi Ayu is to invite direct student interaction, provide information and provide convenient services. (2) Intervention through the use of media and learning materials, namely the teacher uses reading materials such as books, letter toys and readings on the classroom wall (3) Remedial, namely the teacher applies remedial to all subjects in order to provide comparisons and of course the questions given lower weight than the original problem.